Pemanfaatan Media Sisa Tanam Padi Sawah Periode Pertama sebagai Media Tanam Periode Kedua - Galih Purwo Styono; Anis Sholihah; Siti Muslikah (AGRONISMA, 2019)
This study aims to find out the effect of a mixture of compost and straw kiapu various compositions giving rest The first planting period on growth and yield of rice paddy second period. The design used is simple RAK, treatment (R1- + = 100% standard; R2- + = 75% + 25% standard rice straw; DIR3 + 50% + 50% standard rice straw; R4- + = 25% kiapu + 75% straw; R5- + = 100% straw) plus NPK treatment and control , The results showed the growth of rice on average in the rest of the grant 50% + 50% standard rice straw (long crop of96.08cm, number of leaves most 270.50strands, number of tillers 67.33 tillers and leaf area 11347.09 cm2) and best treatment DIR3 production (50% Pistia + 50% straw) with a dry weight of panicle 106.67 g.pot-1 and weighed 8:53 ton.ha weight per ha-1.